Problematic smartphone usage, objective smartphone engagement, and executive functions: A latent variable analysis - HARTANTO, Andree (Institutional Knowledge at Singapore Management University, 2023)
The negative consequences of smartphone usage have seen frequent discourse in popular media. While existing studies seek to resolve these debates in relation to executive functions, findings are still limited and mixed. This is partly due to the lack of conceptual clarity about smartphone usage, the use of self-reported measures, and problems related to task impurity. Addressing these limitations, the current study utilizes a latent variable approach to examine various types of smartphone usage, including objectively measured data-logged screen time and screen-checking, and nine executive function tasks in 260 young adults through a multi-session study. Our structural equation models showed no evidence that self-reported normative smartphone usage, objective screen time, and objective screen-checking are associated with deficits in latent factors of inhibitory control, task-switching, and working memory capacity. Only self-reported problematic smartphone usage was associated with deficits in latent factor task-switching. These findings shed light on the boundary conditions of the link between smartphone usage and executive functions and suggest that smartphone usage in moderation may not have inherent harms on cognitive functions.